L5 Root Compression Due to Facet Synovial Cyst (Revista de Medicina Clinica, 2020)
Introduction: Low back pain with root compression represents a symptomatology frequently seen in the rehabilitation departments. Lumbar synovial facetary cysts are rare, being lesions related with facet joints degenerations. Its predominant location is at L4-L5 level, magnetic resonance imaging is the choice method for its diagnosis. Surgery is the best alternative if there is persistent pain and neurologicalsymptoms. Case Report: A 51-year-old female patient, without a history of interest, who went to the Rehabilitation consultation with three-month L5 root compression evolution, which did not respond to the prescribed pharmacological treatment. Whit L4/L5 synovial cyst diagnosed by magnetic resonance, She was sent to Neurosurgery, performing hemilaminectomy and cystectomy and rehabilitation program, discharging asymptomatic patient. Conclusion: Low back pain due to root compression due to facet synovial cyst is rare, however it mustbe part of the differential diagnosis.